Working and Learning in Times of Uncertainty: Challenges to Adult, Professional and Vocational Education - Bohlinger, Sandra; Haake, Ulrika; Jørgensen, Christian Helms; Toiviainen, Hanna; Wallo, Andreas (Research on the education and learning of adults, 2015)
FREELY AVAILABLE ONLINE AS OPEN ACCESS BOOK! This book analyses the challenges of globalisation and uncertainty impacting on working and learning at individual, organisational and societal levels. Each of the contributions addresses two overall questions: How is working and learning affected by uncertainty and globalisation? And, in what ways do individuals, organisations, political actors and education systems respond to these challenges? Part 1 focuses on the micro level of working and learning for understanding the learning processes from an individual point of view by reflecting on learners' needs and situations at work and in school-work transitions. Part 2 addresses the meso level by discussing sector-specific and organisational approaches to working and learning in times of uncertainty. The chapters represent a broad range of branches including public services (police work), the automotive sector and the health sector (elderly care). Finally, Part 3 addresses the macro level of working and learning by analysing how to govern, structure and organise vocational, professional and adult education at the boundaries of work, education and policy making.